Needs Assessment of Digital Video-Based Anaemia Education for Prospective Brides in Premarital Health Services at Public Health Centres in Bengkalis District - Sahrizal, M; Salu, Amos Rante; Djannah, Sitti Nur; Trisnowati, Heni (Reflection Journal, 2026)
Anaemia among women of reproductive age remains a public health concern because it may affect preconception readiness, pregnancy outcomes, and maternal and fetal health. Prospective brides are a strategic group for receiving anaemia education before pregnancy. This study aimed to analyse the need for digital video-based anaemia education among prospective brides attending premarital health services at public health centres in Bengkalis District. This preliminary study used a descriptive quantitative approach with a needs assessment design. The study was conducted in January 2026 and involved 30 prospective brides selected through total sampling. Data were collected using a structured questionnaire with yes/no responses covering basic knowledge of anaemia, reproductive and pregnancy-related impacts, prevention efforts, previous information sources, perceptions of anaemia as a premarital health issue, educational needs, perceptions of digital media, feasibility of video media, media availability, and willingness to receive digital video-based education. Data were analysed descriptively using frequencies and percentages. The need percentage was calculated by dividing the total number of “yes” responses by the total responses across all subitems. The results showed that 94.42% of responses were “yes” and 5.58% were “no”. Most respondents were aged 20–25 years and had an undergraduate educational background. These findings indicate high acceptance and perceived need for digital video-based anaemia education as an initial basis for developing premarital educational media. However, this study did not evaluate the effectiveness of the media in improving knowledge, attitudes, or preventive behaviour